Efficacy and precision of fecal genotyping to estimate coyote abundance. (14th November 2016) - Gulsby, William D.; Killmaster, Charlie H.; Bowers, John W.; Laufenberg, Jared S.; Sacks, Benjamin N.; Statham, Mark J.; Miller, Karl V.
ABSTRACT: Questions concerning the effects on other wildlife species by coyotes ( Canis latrans ) in recently colonized areas, including the southeastern United States, continue to receive attention in the literature. Coyote abundance estimates, achieved via genetic sampling of feces, can be useful in answering such questions. However, rapid degradation of fecal DNA in humid subtropical climates, like that of the southeastern United States, may limit the efficacy of the technique. To evaluate this hypothesis, we collected and analyzed 434 suspected coyote scats from February 2010 to April 2012 on 2 sites in central Georgia, USA. We quantified seasonal and comprehensive genotyping success, and the effect of sampling effort on precision of closed population abundance estimates. We successfully species‐typed 316 (73%) scats, 219 (69%) of which belonged to coyotes. Of those, 136 (62%) yielded multilocus genotypes. The seasonal probability of genotyping a scat ranged from 0.53 to 0.71. Scats collected during spring were more likely to yield consensus genotypes, but the overall effect of season on genotyping success was minimal. The median CV for model‐averaged N ˆ (i.e., coyote abundance) using the complete data set was relatively precise (<15%). Precision of abundance estimates decreased with decreasing sampling effort, but CV values remained <20% with up to a 25% reduction in effort. Our findings related to genotyping success demonstrate noninvasive genetic sampling of feces is a promising technique for estimating coyote abundance in humid subtropical climates. Combined with our results regarding sampling effort, these findings can aid in designing surveys capable of achieving desired objectives in similar environments. © 2016 The Wildlife Society. Abstract : We report on success rates associated with the use of fecal genotyping to estimate coyote abundance in the southeastern United States and other regions with humid, subtropical climates. Considerations for future experimental design are presented based on our results.